KODOMO SHOKUDOU AS THE THIRD SPACE DURING COVID-19 PANDEMIC: KODOMO SHOKUDOU SEBAGAI RUANG KETIGA DI TENGAH PANDEMI COVID-19 - Aurora Dyah Nareshwari; Wawat Rahwati; Ucu Fadhilah (Jurnal Kata, 2024)
This research investigates the role of kodomo shokudou as a public facility for the local community, particularly during the COVID-19 pandemic. Through case studies of Hagu Shokudou, Nishinari Kodomo Shokudou, and Kirin no Ie in Osaka, this study aims to analyze how these facilities function within their perspective communities and how the local community perceives their presence during the pandemic.  This study aims to analyze how local people perceive their presence and their role in providing healthy food during the pandemic. This research was conducted by using Edward Soja’s spatial concept and digital ethnographic methods such as website searches, video documentaries, and digital communication. This result reveals that three kodomo shokudou’s serve as the third spaces of providing healthy and affordable meals while evoking the atmosphere of the first space (family) and the second space (school), elements often missing for students during the pandemic.